Facial nerve palsy, parotid mass and Epstein–Barr virus. (January 2016) - Grover, Nancy; Leake, John; Malicki, Denise; Khanna, Paritosh; Pransky, Seth
Abstract: We report the case of a seven year old girl with 22q11 deletion mosaicism who presented with a sudden onset rapidly enlarging left parotid mass and ipsilateral facial nerve paresis. MRI and cytology were inconclusive. She underwent partial superficial parotidectomy to obtain definitive histopathology, which was reported as suggestive of acute Epstein Barr infection. A subsequent quantitative Epstein–Barr Virus (EBV) PCR clinched the diagnosis four weeks after her initial presentation. She was stared on oral Valgancyclovir and her facial nerve showed recovery. We discuss the challenges faced in managing this case with delayed conclusive diagnosis of acute Epstein Barr virus infection.